Pengaruh Penggunaan Afo Fleksibel Dan Afo Jointed Plantar Fleksi Stop Terhadap Kecepatan Berjalan Pasien Dengan Hemiparetic Cerebrovascular Accident ( CVA ) - Agus Setyo Nugroho; M. Syafi’i; Sri Surini Pudjiastuti (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract : Drop Foot, AFO Fleksibel, AFO Jointed Plantar Stop, Walking Speed, CVA. Research Objectives To determine whether there is a difference in the use of AFO Flexible and AFO Jointed Plantar Stop against the walking speed of someone who has drop foot because of CVA. The experimental quasy research method used two group pre and post test design approach. The study population was patients who had drop foot because of CVA. Statistical test result with paired t test at Flexible AFO user group walking speed shows p value 0,000 <0,05 so there is Flexible AFO effect to different speed of walking in drop foot sufferer. Result of statistical test with paired t test at walk time of user group of AFO Jointed Plantar Stop shows p value 0,000 <0,05 so there is influence of AFO Jointed Plantar Stop to difference of walking time in patient of drop foot. Statistical test results with paired t test at the walking speed of AFO Jointed Plantar Stop user group showed p value 0,000 <0,05 so that there is influence of AFO Jointed Plantar Stop to difference of walking speed in drop foot sufferer. The result of statistical test with paired t test at walk time of AFO Flexible user group with AFO Jointed Plantar Stop shows p value 0,013 <0,05 so there is time difference walking using AFO Flexible with AFO Jointed Plantar Stop on walking time in drop foot sufferer. The result of statistical test with paired t test at Flexible AFO user group speed with AFO Jointed Plantar Stop shows p value 0,012 <0,05 so there is difference of walking speed using AFO Flexible with AFO Jointed Plantar Stop to walking speed at patient of foot foot.Dengan Conclusion The use of AFO Flexible has a better walkspeed effect compared to the use of AFO Jointed plantar stop with an average difference of 0.010